ASPEK HUKUM PEMBUKTIAN E-MAIL YANG BERUPA AKTA - Mirah Kristina Dewi, I Gusti Ayu; Oka Parwata, Anak Agung (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013, 2013)
The sophistication of Internet technological can through the boundaries of time anddistance, so the physical boundaries of the state is no longer a barrier to communicationand interaction of the various interests of the community. The ability of the Internet haschanged the way of thinking, interacting and act that also impacts the law. The law isusually based on something real (physical) but the Internet has changed the real thing intosomething that is electronically, like send a letter via e-mail. This means it requires a broadunderstanding of the evidence in a civil case and to ensure the certainty of civil law Indonesia.
Keywords: E-Mail, Verification